JURIDICAL ANALYSIS OF SALE AND PURCHASE AGREEMENTS VIA THE INTERNET ACCORDING TO LAW NUMBER 19 OF 2016 - Siti Afiyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
E-commerce is the outcome of applying information technology, enabling transactions between producers and consumers through the internet. This paper addresses two main issues: the validity of online buying and selling, and the responsibilities of the parties involved as stipulated in Law no. 19 of 2016, which amends Law Number 11 of 2008 on Information and Electronic Transactions. The research methodology employed is normative legal research. The findings indicate that the requirements for e-commerce transactions are not fully met, particularly in terms of verifying the parties' skills and authorization to engage in legal actions. However, as long as the transaction does not harm either party, it is considered valid. Legal protection for parties involved in online sales and purchase agreements includes the agreement itself, which is established through mutually agreed-upon rules, as well as the privacy protection outlined in Article 25 of the ITE Law, which safeguards the personal data of both merchants and customers.